Global Supply Chains and Trade Policy Responses to the 2008 Crisis - Gawande, Kishore; Hoekman, Bernard; Cui, Yue (Oxford University Press on behalf of the World Bank, 2016)
The collapse in trade and the contraction of output that occurred during 2008–9 was comparable to, and in many countries more severe than, the Great Depression of the 1930s. However, it did not give rise to the rampant protectionism that followed the Great Crash. The idea that the rise in the fragmentation of production across global value chains – vertical specialization – may be a deterrent against protectionism is underappreciated in the literature. Institutions also played a role in limiting the extent of protectionist responses. World Trade Organization discipline raises the cost of using trade policies for member countries and has proved to be a stable foundation for the open multilateral trading system that has been built over the past 50 years. Using trade and protection data for seven large emerging market countries that have a history of active use of trade policy, the influence of these and other factors on trade policy responses to the 2008 crisis are empirically examined. An instrumental variables strategy is used to identify their impact. Participation in global value chains is found to be a powerful economic factor determining trade policy responses.